Abrupt climate change at ~2800 yr BP evidenced by a stalagmite record from peninsular India. (November 2018) - Sinha, Nitesh; Gandhi, Naveen; Chakraborty, S; Krishnan, R; Yadava, MG; Ramesh, R
This study presents an analysis of the Indian summer monsoon (ISM) rainfall variations for a 1460-year period (1720–3180, Before Present BP: 1950 AD), based on a long record of stable isotopic variations (δ 18 O) with high temporal resolution (~annual) obtained from a U-Th dated stalagmite from the Kadapa cave in peninsular India. This stalagmite proxy record captures variations associated with wet and dry monsoons on decadal to centennial time-scales, together with a general declining trend in the ISM during the 1460-year period. It is noted that the declining trend of the ISM follows the northern hemispheric summer insolation, which is known to influence the location and strength of the Inter tropical convergence zone (ICTZ). The stalagmite record also indicates an abrupt climate change, characterized by the decline of ISM around 2800 yr BP, as manifested in the enrichment of 18 O values. Furthermore, the enriched 18 O values around 2800 yr BP are corroborated by changes in the stalagmite growth rate, its trace elemental ratios (Sr/Ca, Ba/Ca and U/Ca) and crystallographic structure. In addition, the decline of ISM around 2800 yr BP coincides with a sudden rise in the atmospheric Δ 14 C, indicative of reduced solar activity. This period around 2800 yr BP is widely reported as the cold European climate associated with ice debris events in the North Atlantic (also known as the Iron Age Cold Epoch), which were reportedly forced by low solar activity. Syntheses of other available stalagmite records from the Indian region, during the common time-frame, show coherent variations with the Kadapa stalagmite and also the Dongge cave stalagmite (southern China), pointing to synchronous variations of the Indian and the East Asian monsoon systems.